# 6.5 The dimension formula

- Page ID
- 275

\( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

\( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

The next theorem is the key result of this chapter. It relates the dimension of the kernel and range of a linear map.

**Theorem 6.5.1. ***Let* \(V \) *be a finite-dimensional vector space and* \(T:V\to W \) *be a linear map. Then* \(\range(T) \) *is a finite-dimensional subspace of* \(W \) *and*

\[ \begin{equation} \label{eq:dim formula}

\dim(V) = \dim(\kernel(T)) + \dim(\range(T)). \tag{6.5.1}

\end{equation}\]

*Proof. *

Let \(V \) be a finite-dimensional vector space and \(T\in \mathcal{L}(V,W) \). Since \(\kernel(T) \) is a subspace of \(V \), we know that \( \kernel(T) \) has a basis \((u_1,\ldots, u_m) \). This implies that \(\dim(\kernel(T))=m \). By the **Basis Extension Theorem**, it follows that \( (u_1,\ldots,u_m) \) can be extended to a basis of \(V \), say \((u_1,\ldots,u_m,v_1,\ldots,v_n) \), so that \(\dim(V)=m+n \).

The theorem will follow by showing that \((Tv_1,\ldots, Tv_n) \) is a basis of \(\range(T) \) since this would imply that \(\range(T) \) is finite-dimensional and \(\dim(\range(T))=n \), proving Equation 6.5.1.

Since \((u_1,\ldots,u_m,v_1,\ldots,v_n) \) spans \(V \), every \(v\in V \) can be written as a linear combination of these vectors; i.e.,

\begin{equation*}

v = a_1 u_1 + \cdots + a_m u_m + b_1 v_1 + \cdots + b_n v_n,

\end{equation*}

where \(a_i,b_j\in \mathbb{F} \). Applying \(T \) to \(v \), we obtain

\begin{equation*}

Tv = b_1 T v_1 + \cdots + b_n T v_n,

\end{equation*}

where the terms \(Tu_i \) disappeared since \(u_i\in \kernel(T) \). This shows that \((Tv_1,\ldots, Tv_n) \) indeed spans \(\range(T) \).

To show that \((Tv_1,\ldots, Tv_n) \) is a basis of \(\range(T) \), it remains to show that this list is linearly independent. Assume that \(c_1,\ldots, c_n \in \mathbb{F} \) are such that

\[ c_1 T v_1 + \cdots + c_n T v_n =0.\]

By linearity of \(T \), this implies that

\[ T(c_1 v_1 + \cdots + c_n v_n) = 0, \]

and so \(c_1 v_1 + \cdots + c_n v_n\in \kernel(T) \). Since \((u_1,\ldots,u_m) \) is a basis of \(\kernel(T) \), there must exist scalars \(d_1,\ldots,d_m\in\mathbb{F} \) such that

\begin{equation*}

c_1 v_1 + \cdots + c_n v_n = d_1 u_1 + \cdots + d_m u_m.

\end{equation*}

However, by the linear independence of \((u_1,\ldots, u_m,v_1,\ldots, v_n) \), this implies that all coefficients \(c_1=\cdots =c_n=d_1=\cdots =d_m=0 \). Thus, \((Tv_1,\ldots, Tv_n)\) is linearly independent, and we are done.

**Example 6.5.2.** Recall that the linear map \(T:\mathbb{R}^2 \to \mathbb{R}^2 \) defined by \(T(x,y)=(x-2y,3x+y) \) has \(\kernel(T)=\{0\} \) and \(\range(T)=\mathbb{R}^2 \). It follows that

\[ \dim(\mathbb{R}^2) = 2 = 0+2 =\dim(\kernel(T)) + \dim(\range(T)). \]

**Corollary 6.5.3. ***Let* \(T\)* in* \(\mathcal{L}(V,W) \).

*If*\(\dim(V)>\dim(W) \),*then*\(T \)*is not injective.**If*\(\dim(V)<\dim(W) \),*then*\(T \)*is not surjective*.

*Proof.*

By Theorem 6.5.1, we have that

\begin{equation*}

\begin{split}

\dim(\kernel(T)) &= \dim(V) - \dim(\range(T))\\

&\ge \dim(V) - \dim(W)>0.

\end{split}

\end{equation*}

Since \(T \) is injective if and only if \(\dim(\kernel(T))=0 \), \(T \) cannot be injective.

Similarly,

\begin{equation*}

\begin{split}

\dim(\range(T)) &= \dim(V) - \dim(\kernel(T))\\

&\le \dim(V) < \dim(W),

\end{split}

\end{equation*}

and so \(\range(T) \) cannot be equal to \(W \). Hence, \(T \) cannot be surjective.

### Contributors

- Isaiah Lankham, Mathematics Department at UC Davis
- Bruno Nachtergaele, Mathematics Department at UC Davis
- Anne Schilling, Mathematics Department at UC Davis

Both hardbound and softbound versions of this textbook are available online at WorldScientific.com.